Black–white differences in cancer risk in Harare, Zimbabwe, during 1991–2010. Issue 6 (19th October 2015) - Chokunonga, Eric; Windridge, Peter; Sasieni, Peter; Borok, Margaret; Parkin, D. Maxwell
Abstract : Data from 20 years of cancer registration in Harare (Zimbabwe) are used to investigate the risk of cancer in the white population of the city (of European origin), relative to that in blacks (of African origin). In the absence of information on the respective populations‐at‐risk, we calculated odds of each major cancer among all cancers, and took the odds ratios of whites to blacks. Some major differences reflect obvious phenotypic differences (the very high incidence of skin cancer—melanoma and nonmelanoma—in the white population), whereas others (high rates of liver cancer, Kaposi sarcoma and conjunctival cancers in blacks) are the result of differences in exposure to infectious agents. Of particular interest are cancers related to lifestyle factors, and how the differences in risk are changing over time, as a result of evolving lifestyles. Thus, the high risk of cancers of the esophagus and cervix uteri in blacks (relative to whites) and colorectal cancers in whites show little change over time. Conversely, the odds of breast cancer, on average four times higher in whites than blacks, has shown a significant decrease in the differential over time. Cancer of the prostate, with the odds initially (1991–1997) 15% higher in whites had become 33% higher in blacks by 2004–2010. Abstract : What's new? The risk of cancer frequently varies between ethnic groups, raising the question of how much those variations are due to inherent genetic differences versus environmental exposures. In this comparison of cancer risk among whites and blacks in Harare, Zimbabwe, over the period 1991–2010, both obvious and relatively obscure risk variations were identified. Prominent among the latter were changes in risk differential for certain cancers, including breast cancer, the incidence of which is rising in the black population. Changes in cancer risk differential likely are due in part to shifting lifestyle trends among white and black populations in Harare.